2017
DOI: 10.1021/jacs.7b10833
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of a μ-oxo Dicopper(II) Complex for Hydrogen Atom Abstraction

Abstract: The mono-μ-hydroxo complex {[Cu(tmpa)]-(μ-OH)} (1) can undergo reversible deprotonation at -30 °C to yield {[Cu(tmpa)]-(μ-O)} (2). This species is basic with a pK of 24.3. 2 is competent for concerted proton-electron transfer from TEMPOH, but is an intrinsically poor hydrogen atom abstractor (BDFE(OH) of 77.2 kcal/mol) based on kinetic and thermodynamic analyses. Nonetheless, DFT calculations experimentally calibrated against 2 reveal that [CuO] is likely thermodynamically viable in copper-dependent methane mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 19 publications
1
42
1
2
Order By: Relevance
“…Experiments found to be consistent with this result were that the complex could react with substrates containing weak C–H and O–H bonds (cyclohexadiene and TEMPO-H), giving the products benzene and TEMPO, respectively (Scheme 20). 811 While very strong C–H bonds, such as methane, could not be oxidized, this is the first indepth study obtaining thermodynamic parameters relevant to oxidation by a [Cu 2 O] 2+ species.…”
Section: Copper Chemistry With Dioxygen: Biology and Model Systemsmentioning
confidence: 89%
See 1 more Smart Citation
“…Experiments found to be consistent with this result were that the complex could react with substrates containing weak C–H and O–H bonds (cyclohexadiene and TEMPO-H), giving the products benzene and TEMPO, respectively (Scheme 20). 811 While very strong C–H bonds, such as methane, could not be oxidized, this is the first indepth study obtaining thermodynamic parameters relevant to oxidation by a [Cu 2 O] 2+ species.…”
Section: Copper Chemistry With Dioxygen: Biology and Model Systemsmentioning
confidence: 89%
“…Most recently, Kieber-Emmons and co-workers 811 published on the thermodynamic parameters of hydrogen-atom-transfer reactivity by a model [Cu 2 O] 2+ complex. Titration of a structurally characterized ( μ -hydroxo)dicopper(II) complex bearing the TMPA ligand with the base 1,8- diazabicyclo[5.4.0]undec-7-ene (DBU) allowed for the determination of the pK a of the bound hydroxide ligand (pK a = 24.3 ± 1.9 in MeCN).…”
Section: Copper Chemistry With Dioxygen: Biology and Model Systemsmentioning
confidence: 99%
“…Kieber‐Emmons et al recently reported the reaction of a dicopper(II)‐μ‐oxo adduct with TEMPOH, which resulted in the formation of a dicopper(I,II)‐μ‐hydroxo adduct via a concerted HAT mechanism. Kinetic study of the reaction revealed activation parameters of Δ H ‡ = 5.3 ± 2.8 kcal · mol –1 and Δ S ‡ = –44 ± 11 cal · K –1 · mol –1 , and a KIE (= k H / k D ) of 1.6 ± 0.3 …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the O–H bond dissociation energy of 6 is suggested to be around 80 kcal · mol –1 . Of note, the O–H bond dissociation energy of Meyer's μ‐1,1‐hydroperoxo dicopper(II) complex was estimated as 72 kcal · mol –1[58] and Kieber‐Emmons's dicopper(I,II)‐ μ ‐hydroxo complex as 77.2 kcal · mol –1 …”
Section: Resultsmentioning
confidence: 99%
“…[17] They indeed showed that the reaction of the Mn III (OO -) with benzoic anhydride yielded the manganese-acylperoxo intermediate that gave a Mn V O resulting from the O-O heterolysis favoured by 1-methyl imidazole as an axial ligand (push effect). [16] and [28]).…”
Section: Mononuclear Metal Complexesmentioning
confidence: 98%